Penerapan Permainan Grab The Ball Terhadap Peningkatan Hasil Belajar Gerak Dasar Passing Bawah Pada Permainan Bola Voli - Defita Rahma Dwi Utami; Mochamad Ridwan; Lestari Suryaningsih (Concept: Journal of Social Humanities and Education, 2025)
The early outcomes of teaching fundamental passing techniques in volleyball games to the students of class IV-A at SDN Jeruk 1/469 Surabaya were unsatisfactory, with a significant number of pupils failing to fulfil the expected performance standards (KKTP). This is demonstrated by the fact that only 50% of students in this class have successfully finished or satisfied the KKTP. Researchers were motivated to carry out Classroom Action Research (PTK) in this class utilising the grab the ball game method. The objective is to enhance academic achievements in class IV-A at SDN Jeruk 1/469 Surabaya. Substantial outcomes were achieved after implementing this methodology. The methodology is executed in two rounds. During cycle I, there was a 20% increase, going from 50% to 70%. Additionally, during cycle II, there was a notable improvement in student learning outcomes. In cycle I, the percentage of students achieving satisfactory results was 70%, but it increased to 80% in cycle II. Based on these results, it can be inferred that implementing the grab the ball game can enhance the learning outcomes of basic volleyball underpassing movement material for class IV-A students at SDN Jeruk 1/469 Surabaya.